A IMPORTÂNCIA DOS ACERVOS JUDICIAIS PARA A PESQUISA EM HISTÓRIA: um percurso - Monica Duarte Dantas; Filipe Nicoletti Ribeiro (TRF2, 2020)
In this article the authors aim to highlight the importance of judicial records as privileged sources for the making of historical narratives concerning 19th century Brazil. Without access to criminal and civil records, available in numerous archives scattered in the country, a handful of researches -from the onset of academic thesis and dissertations, groundbreaking works in the 1980s, until innovative oeuvreswritten in the last years and decades -would have never been possible.